An analysis of English adjectives describing human skin colours and their equivalents in Vietnamese - Quang, Van Viet Cuong (2020)
Đồng ý về việc phục vụ đọc trực tuyến, cho chép file và cho photo 100% tài liệu; References: p.i - iii; Master thesis of Thu Dau Mot University. Major: English language; Code: 8220201; 5 chapters: Introduction; Literature review; Methodology; Findings And Discussion; Conclusion and implications